21ST CENTURY SKILLS OF ECONOMIC INTELLIGENCE RELATED TO THE RESILIENCE OF THE NATIONAL ECONOMY - Anis, Aswhar; Susdarwono, Endro Tri (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2019)
Indonesia is an agricultural country, but imports rice, sugar, wheat flour, maize, milk powder, onions, garlic, soybeans, carrots, from abroad. In all countries of the world, agriculture is the most protected sector of the economy. Food security is important. If a country imports most of its food products from other countries to fulfill its need because the price is lower than domestic prices, then the country will become dependent in its food supply on other countries for the future. This will be dangerous. So that 21st century skills are needed towards economic intelligence in Indonesia who can be relied on in terms of national economic resilience. These skills include : Ecological: the business environtment, Psycho-sociological: internal actors of organisation, Reticulated: external human networks claimed and moblized around the project, Teleological: final purpose of the approach through strategy development,Â Technological: includes all the methods, tools and techniques used for the entire process of decision support through surveillance process, information protection, or benchmarking. Economic intelligence concerns the set of concepts, methods and tools which unify all the co-ordinated actions of research, acquisition, treatment, storage and diffusion of information, relevant to individual or clustered enterprises and organisations in the framework of a strategy.